FAKTOR EMISI ENERGI TIDAK TERBARUKAN PADA PEMBANGKIT LISTRIK JAWA TIMUR - Kusuma, Maritha Nilam (Journal of Research and Technology, 2015)
Carbon emission that emited by electric plant in Jawa timur could be estimated. Estimation was done by emission factor calculation first. Emission factor was multipled with electric consumption value to got emmison carbon value. The method used ACM0002 that issued by CDM-PDD Version02 IPCC. Data supporting are NVC, SFC and CEF. The result could be found that coal and natural gas have emmision there are 1,00688434 Ton CO2/Mwh and 0,392860328 Ton CO2/Mwh. Keywords: carbon emission, emission factor, and electric plant